Kredit Bermasalah sebagai Pemoderasi Pengaruh Tingkat Penyaluran Kredit terhadap Profitabilitas - Sukirno Sukirno (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
Abstract This study aims to empirically challenge the moderation of Non-Performing Loans to the effect of Credit Distribution Rates on Profitability. The population of 81 bank companies listed on the Indonesia Stock Exchange in the period 2014-2018 and which met the criteria of the research sample (purposive sampling) were 22 companies. The research method uses survey methods with quantitative research approaches, the analytical tool used is moderation regression. This study concludes that the level of credit distribution has a significant positive effect on profitability and the existence of the problem loan variable is proven to be a moderating variable that weakens the relationship between the level of credit distribution and profitability.